(untitled) (Academic Journal of Internal Affairs, 2021)
As one of the peer reviewers of the Law Enforcement Lexicon I state with full professional conviction that publication of this lexicon created a work of genre-historical importance for our law enforcement science reaching its teenage years. I would also like to record at the beginning of my reflection that I want neither praise nor blame this gigantic publication. In my notice I intend to stay impartial, objective and neutral even though I expressed my definitive recognition in the introducing sentence. This recognition means, according to my intention, rather thanks. So, I have to thank for the authors and editors as they gave a present to active contributors of law enforcement science, for people interested in it and for a wider reader public by this work appropriate to the present level of our law enforcement culture.